Productive Waqf with Money (Cash Waqf) in the View of the Acehnese Dayah Scholars - Anwar Anwar; Nawir Yuslem; Syafruddin Syam (Faculty of Law, Universitas Pekalongan, 2022)
This study focuses on exploring the views of the dayah scholars in Aceh and the dynamics behind their different views on cash waqf which are becoming popular in Indonesian society. Designed in the form of a qualitative research, research data were collected through in-depth interviews with 8 prominent dayah scholars in Aceh, who were selected purposively. The eight scholars who were used as key informants for this research were charismatic scholars who were always used by the people of Aceh as the mecca of legal fatwas. Data were also collected through repeated observations to research sites and document studies related to the topic being researched. The results of the study show that the dayah scholars in Aceh have different views in executing the law allowing cash waqf. This difference occurs because each scholar has a different perspective in understanding the source of waqf law, both in terms of text and context. In the end, this study argues that the view of the dayah scholars regarding cash waqf which has been very textual in nature, must be shifted to contextual, so that the implementation of cash waqf is carried out properly as an effort to improve the welfare of the Acehnese people.